2016
DOI: 10.1093/cid/ciw002
|View full text |Cite
|
Sign up to set email alerts
|

Surgery as an Adjunctive Treatment for Multidrug-Resistant Tuberculosis: An Individual Patient Data Metaanalysis

Abstract: Partial lung resection, but not pneumonectomy, was associated with improved treatment success among patients with MDR-tuberculosis. Although improved outcomes may reflect patient selection, partial lung resection surgery after culture conversion may improve treatment outcomes in patients who receive optimal medical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 12 publications
0
52
0
4
Order By: Relevance
“…Evidence for the effectiveness of different forms of elective pulmonary surgery in MDR-TB patients was derived from an IPD meta-analysis of 26 cohorts, as well as a systematic review and study-level meta-analysis [47, 48]. Two sets of analyses were undertaken: for partial pulmonary resection and for radical pneumonectomy.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence for the effectiveness of different forms of elective pulmonary surgery in MDR-TB patients was derived from an IPD meta-analysis of 26 cohorts, as well as a systematic review and study-level meta-analysis [47, 48]. Two sets of analyses were undertaken: for partial pulmonary resection and for radical pneumonectomy.…”
Section: Resultsmentioning
confidence: 99%
“…Positron emission tomography–computed tomography (PET‐CT) scans can help to identify patients at risk for relapse although the interpretation of metabolically active infiltrations is still difficult . Although the level of evidence was reported as being low, certain patients with localized infiltrations may benefit from surgical interventions after culture conversion . Carefully selected patients may also improve their immune system's capability to control the bacteria by host‐directed therapeutic interventions .…”
Section: Individualized Therapy Versus Standardized Treatment Regimenmentioning
confidence: 99%
“…112 Although the level of evidence was reported as being low, certain patients with localized infiltrations may benefit from surgical interventions after culture conversion. 113,114 Carefully selected patients may also improve their immune system's capability to control the bacteria by host-directed therapeutic interventions. 115 As an example for a host-aimed intervention, vitamin D supplementation has not led to significant improvement of treatment outcomes except for certain subgroups of patients with specific genetic polymorphisms.…”
Section: Individualized Therapy Versus Standardized Treatment Regimenmentioning
confidence: 99%
“…A recent meta-analysis showed that partial lung resections were associated with better treatment outcomes for MDR-TB compared with no surgical procedure. 10 The timing of the surgical procedure is another point that is still unclear. The WHO currently recommends that resection surgery for MDR-TB should be timed to allow the best chances of cure with the least morbidity.…”
Section: Discussionmentioning
confidence: 99%